L’interaction comme problème et solution en EMS psychogériatrique - Fabienne Malbois (Revue d'anthropologie des connaissances)
Based on the idea that the “logic of care” is sensitive to context, this article gives empirical consistency to the experimental attitude that is characteristic of person-centred approaches in psychogeriatric nursing homes. It begins by describing the style of care deployed in the case studied, in particular the way in which it provides a place for the sensing subject. It then sets out to characterise the three forms of professional enquiry to which this style of care gives rise, and their specific tests. Particular attention is paid to the different ways in which the problematic experiences of residents are transformed (manipulation, adjustment, fabrication), to the roles played by observation - and therefore the eye - in the conduct of these processes, and to the different arts of doing, or practical knowledge, involved.